Compliance with the Use of Radiation Protection Equipment in the Panoramic Room of the Radiology Installation at Ken Saras Hospital - Arifah, Siti (NHM PRESS, 2023)
The use of radiation protection devices in the radiology installation is very important to dispel scatter radiation and reduce the effects of radiation, but during an examination in the panoramic room of the radiology installation, Ken Saras Hospital, Kab. Semarang radiographers do not use aprons on patients or themselves, for this reason this research was conducted with the aim of knowing radiographer compliance in using radiation protection devices and radiation protection procedures in the panoramic room of the radiology installation at Ken Saras Hospital, Kab. Semarang. This type of research is qualitative research with a case study approach which was carried out in June 2023 with the object of research in the form of an apron. The data in this study were obtained through observation and interviews with 1 radiation protection officer and 3 radiographers who served in the panoramic room of the radiology installation at Ken Saras Hospital, Kab. Semarang. The results showed that the radiographer did not use the apron available in the panoramic room and only used radiation shields, but the radiographer took other protective measures. The conclusion in this study is that radiographers comply in implementing radiation protection measures against themselves by using radiation protection devices in the form of radiation shields while radiation protection for patients is not carried out by providing aprons but through other protective measures in accordance with the principles of radiation protection, namely justification, optimization and limitation .